Interspecific hybridization between Cajanus cajan (L.) Millsp. and C. lanceolatus (WV Fitgz) van der Maesen. Issue 2 (28th August 2013) - Srikanth, Sandhya; Rao, M. V.; Mallikarjuna, Nalini
Abstract : Cultivated pigeonpea has a narrow genetic base. Wild relatives play an important role in the efforts to broaden its genetic base. In this report, we present a successful wide-cross between the cultivated pigeonpea and Cajanus lanceolatus, a wild relative from the secondary gene pool, native to Australia, with desirable traits such as frost and drought resistance. A range of F1 progeny were obtained and the resultant F1 hybrid plants set mature pods and seeds. The hybrids had intermediate morphology, sharing the traits of both the parents. All the F1 hybrids flowered profusely. Some of the hybrids were completely male sterile and some were partially fertile with pollen fertility ranging from 35 to 50 %. Meiotic analysis of the fertile F1 hybrids revealed a high degree of meiotic chromosome pairing between the two parental genomes. Meiotic analysis of the sterile F1 hybrids revealed that the breakdown of microsporogenesis occurred at the post-meiotic stage after the formation of tetrads. Fertile plants formed regular bivalents with normal disjunction, except for occasional asynchrony at meiotic II division.